1992
DOI: 10.3109/00365549209052612
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and the Production of Inflammatory Mediators During the Treatment of Severe Sepsis in Humans

Abstract: Sepsis or septic shock is frequently associated with activation of the complement system, coagulation and fibrinolytic changes and the release of several cytokines. In this study we analyzed the relation of complement activation to the inflammatory mediators, hemodynamic and biochemical parameters and severity of illness and outcome in 20 consecutive patients with clinically defined sepsis. Levels of C3a and C3d were elevated in 90% of the patients (median levels 0.19 mg/l and 8.6 mg/l respectively) in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
2
11
0
3
Order By: Relevance
“…During an observation period of 14 days, nonsurvivors of sepsis had significantly higher NF-kB activity (P <0.001) in their peripheral mononuclear cells than did survivors 52 . In agreement, several studies have reported that nonsurvivors of sepsis [53][54][55][56][57][58][59] and ARDS 59-64 exhibit exaggerated and protracted elevation of circulating pro-inflammatory cytokine levels. In patients with sepsis-induced ARDS we found 59 that elevated pro-inflammatory cytokine levels on day one predicted a persistent elevation over time suggesting that loss of autoregulation is an early event in the course of lethal sepsis.…”
Section: Activation Of the Hpa Axis And Con-trol Of The Host Defense supporting
confidence: 77%
“…During an observation period of 14 days, nonsurvivors of sepsis had significantly higher NF-kB activity (P <0.001) in their peripheral mononuclear cells than did survivors 52 . In agreement, several studies have reported that nonsurvivors of sepsis [53][54][55][56][57][58][59] and ARDS 59-64 exhibit exaggerated and protracted elevation of circulating pro-inflammatory cytokine levels. In patients with sepsis-induced ARDS we found 59 that elevated pro-inflammatory cytokine levels on day one predicted a persistent elevation over time suggesting that loss of autoregulation is an early event in the course of lethal sepsis.…”
Section: Activation Of the Hpa Axis And Con-trol Of The Host Defense supporting
confidence: 77%
“…Furthermore, in nonsurvivors the BAL:plasma ratio for TNF-α, IL-1Β, IL-6 and IL-8 remained unchanged throughout the course of the disease, while it rapidly decreased in survivors [50]. Other groups have also reported nonsurvivors of ARDS or sepsis to have persistent elevation of inflammatory cytokines (table 4) other components of the HDR (i.e., PLA 2 , leukotrines and complement) over time [51,67,[88][89][90]. This finding is important to understanding why treatment modalities of limited duration may be ineffective in ARDS.…”
Section: The Host Defence Response In Ardsmentioning
confidence: 99%
“…Patients with ARDS also have marked and prolonged systemic procoagulant activity and rapid exhaustion of the fibrinolytic system [105]. In sepsis, high levels of PAI-1 are associated with a poor prognosis [106] and correlate with TNF, IL-6 and complement 3a levels [51]. Virtually all ARDS patients have increased circulating FDP levels [107].…”
Section: Coagulationmentioning
confidence: 99%
“…[1,3,4] Many of these alterations have been shown to correlate with an increased rate of sepsis in the posttraumatic and post-operative periods. [5,6] Recently, it has become clear that a cytokine Interleukin-6, earlier known as hybridoma growth factor, is involved in systemic changes associated with tissue injury and infection. [7,8,9] IL-6 is released by damaged tissue and induces the synthesis of proteins in the liver (acute phase proteins) that protect the host against inflammatory reactions, hence has been rightly called the "alarm hormone".…”
Section: Introductionmentioning
confidence: 99%